2017
DOI: 10.1097/md.0000000000007450
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of free-hand fluoroscopic guidance and electromagnetic navigation in distal locking of femoral intramedullary nails

Abstract: Background:Although the method has been used widely, one of the greatest challenges for intramedullary nailing is to position the distal locking screw. A new technology, the electromagnetic navigation system, is a radiation-free way to locate the position of the drill bit and provide 3-dimensional real-time feedback of location and orientation of the drill bit relative to the locking holes. The purpose of our study was to evaluate the reliability and efficiency of the free-hand technique compared to the new el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 22 publications
(26 reference statements)
0
9
0
Order By: Relevance
“…In long bone fractures of the lower extremities, there are studies indicating that the distal locking method with electromagnetic guidance (EMG) system does not make a difference despite studies reporting that it reduces operative time and radiation exposure. [4][5][6]12,13] Studies on distal free hand and magnetic locking intramedullary nails have reported different results concerning operative time, duration of fluoroscopy and radiation exposure. Kirousis et al [18] reported that the mean fluoroscopy duration was 71 seconds in whole intramedullary nailing procedure with free hand technique.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In long bone fractures of the lower extremities, there are studies indicating that the distal locking method with electromagnetic guidance (EMG) system does not make a difference despite studies reporting that it reduces operative time and radiation exposure. [4][5][6]12,13] Studies on distal free hand and magnetic locking intramedullary nails have reported different results concerning operative time, duration of fluoroscopy and radiation exposure. Kirousis et al [18] reported that the mean fluoroscopy duration was 71 seconds in whole intramedullary nailing procedure with free hand technique.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed above, current literature suggests that the EM technique is a better alternative for distal locking in the intramedullary nailing procedure. [1,12,13] However, devices accompanying the EMG-assisted distal screwing systems have the disadvantages of requiring technical skills, a long learning curve, and being uneconomic and unpractical. [2,3] The results of our study showed no difference between the EMG and FHM in tibia fractures.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations